Sudden cardiac arrest in a child with Gitelman syndrome: a case report and literature review - Zieg, Jakub; Tavačová, Terezia; Balaščáková, Miroslava; Peldová, Petra; Fencl, Filip; Kubuš, Peter (Frontiers in Pediatrics, 2023)
Salt-losing tubulopathies are well-recognised diseases predisposing to metabolic disturbances in affected patients. One of the most severe complications can be life-threatening arrhythmias causing sudden cardiac arrest. We present here the first case of a pediatric patient with Gitelman syndrome associated sudden cardiac arrest without precipitating event. A 10-year-old boy collapsed due to ventricular fibrillation in the Prague tram. Lay cardiopulmonary resuscitation was initiated and external defibrillation restored sinus rhythm within minutes. Initial laboratory examination revealed severe hypokalemia requiring large amounts of electrolyte supplementation. Genetic testing focused to tubulopathies was performed and the diagnosis of Gitelman syndrome was made following the identification of two pathogenic variants in SLC12A3 gene (c.2633+1G>A and c.2221G>A). Implantable cardioverter-defibrillator was implanted to prevent sudden cardiac death. The patient was in a good clinical condition with satisfactory electrolyte serum levels at the last follow-up. Causes of electrolyte abnormalities in children should be identified early to prevent the development of rare but potentionally fatal complications.